Beclomethasone dipropionate in microscopic colitis: Results of an exploratory open-label multicentre study (COLCO). Issue 9 (November 2019) - Corte, Thomas De; Janssens, Emilie; D'Hondt, Ann; Thorrez, Koen; Arts, Joris; Dejaegher, Katrien; D'Heygere, François; Holvoet, Annelies; Besien, Bart van; Harlet, Luc; Peeters, Harald; Moerkercke, Wouter Van; et al.
Background: Budesonide has been proven to be an effective treatment for microscopic colitis (MC). However, the two current commercially available preparations are released in the ileum. Beclomethasone dipropionate (Clipper®) is a synthetic corticosteroid with topical colonic release. Objective: This study aimed to explore whether an open-label treatment with beclomethasone dipropionate is an effective treatment for MC. Methods: Prospectively collected data of 30 patients from six centres were retrospectively analysed. All patients had a confirmed diagnosis of idiopathic MC (lymphocytic and collagenous colitis) and were symptomatic (i.e. ≥ 21 loose stools over a seven-day period). Treatment consisted of 10 mg beclomethasone daily for four weeks, followed by 5 mg daily for another four weeks. The primary end point was the proportion of patients in remission (i.e. a mean of < 3 stools/day and a mean of <1 watery stool per day) after an eight-week treatment period. Secondary end points were the proportion of patients responding to therapy at weeks 4 and 8, remission at weeks 4 and 12 and relapse at week 12. Reported adverse events were collected. Results: Overall, at week 8, remission was achieved in 70%, and 77% of patients were responding to treatment. After four weeks of treatment, 80% were responding, and 67% were in remission. Four weeks after stopping treatment, 60% were still in remission. Conclusion: This open-label study suggests that an eight-week course of beclomethasone could be a promising and relatively safe treatment for MC. A randomised controlled study is warranted.